POTENTIAL IMPLEMENTATION OF ETHNOSCIENCE-ORIENTED LEARNING ON BIOTECHNOLOGY MATERIAL - Hijjriyah Anisak; Siti Patonah; M.Syaipul `Hayat (BIOMA : Jurnal Ilmiah Biologi, 2025)
There are still many science learning practices that focus on memorization and do not relate the subject matter to real life or the local cultural context of students. Science is often perceived as a difficult and boring subject because it relies heavily on technical terms and abstract material. This study aims to         explore the potential implementation of     ethnoscience oriented learning in biotechnology material at the junior high school level. Data were collected through interviews with 11 science teachers from Sub Rayon 05 of Grobogan Regency and classroom observations involving 3 peer teachers at SMP Negeri 1 Ngaringan. The        interview was conducted using a Google Form-based questionnaire, while observation data were obtained through direct observation using a structured     observation sheet. The results showed that teachers had a good understanding of ethnoscience (78.7%), and the potential for    implementation was considered very high (84%). However, curriculum development remained the lowest aspect observed (67%). These findings indicate that while the conceptual understanding and enthusiasm of teachers toward ethnoscience are strong, effective implementation           requires systemic support, training, and curricular alignment.